The role of financial financing methods in the development of investment and contracting: Case study National Agency for entrepreneurship support and development - Safia, Amir; Kheira, Nouari (International journal of economic perspectives, 2025)
The study aimed to identify the role of financial financing methods provided by the National Agency for the support and development of entrepreneurship NESDA and its important and prominent role in the development of investment and entrepreneurship in the university environment. Through studying the extent of the contribution of the National Agency for the development of entrepreneurship in the development of investment and entrepreneurship in the university environment, assumptions have been made, including that the National Agency for the support and development of entrepreneurship is one of the most important bodies that provide accompaniment and financial support to students holding investment projects, using descriptive curriculum tools in order to present the general concepts of financing methods available at the agency NESDA and the concepts of investment and entrepreneurship . The study was based on two axes, the first one was devoted to the basic concepts of financing and methods of financing at the NESDA agency, while the second axis was devoted to studying the status of projects funded by the agency.